Holter monitoring in pediatric patients with apparent life threatening events - J P Soni; Anita Baghel; Monika Chaudhary; Manoj Kumar (Journal of Pediatric Critical Care, 2019)
Objectives: To find out utility of Holter monitoring in identifying rhythm abnormalities, its pattern and frequency of occurrence in pediatric patients presenting with an Apparent Life Threatening Event (ALTE). Methods: A prospective observational study conducted on children between 1 to 15 years of age presenting with an apparent life threatening event including breath holding spell, palpitations and syncope. Twelvelead ECG was recorded and then they were subjected to 24 hour Holter monitoring using delta 3 channel Holter. On completion of recording, Holter readings were analysed by a computerised system to look for any rhythm abnormalities, their pattern and frequency.Categorical data of sample were presented as number (%). Chi square test was used to find the significance of study parameters between two groups. Results: Seventy six children were included in the study. In twenty two children, rhythm abnormalities were found with a total diagnostic yield of 28.94%. Twelve (54.5%) children were diagnosed solely by Holter. The abnormalities seen were premature ventricular contractions, premature atrial contractions, AV block, PSVT, WPW syndrome and tachybrady arrhythmia. Conclusion: Rhythm abnormalities are common in children with ALTE. We found one third of the children presenting with ALTE had arrhythmia as the underlying cause. Eight (57.1%) major arrhythmias were diagnosed only by Holter monitoring. We conclude that although the diagnostic yield was low with arrhythmic symptoms in the paediatric age group, it is important in diagnosing silent arrhythmias in high risk groups.